The groundwater intrinsic vulnerability map of S. Eufemia Lamezia Plain (Calabria) - Cuiuli, Enzo (Acque Sotterranee - Italian Journal of Groundwater, 2013)
The study area is the plain of S. Eufemia Lamezia (Calabria) located in correspondence of the homonymous gulf, along the Tyrrhenian coast. The method used for the construction of the vulnerability map of the superficial acquifer of S. Eufemia Lamezia plain is the SINTACS. This method provides an estimate of vulnerability through the calculation of the Vulnerability Index, for each cell, with which it has been discretized the zone of study. The territory has been divided into areas characterized by vulnerability degree from medium to very high, passing through the intermediate terms. In the southern sector of the plain, where the depth of groundwater is variable, between 4,00 m and 0,50 m from the ground level, are located: the industrial/ handcrafted area of Lamezia Terme, the areas with the greatest agricultural and zootechnical yields, tourist facilities and private houses along the coast. They represent a potential pollution risk for the superficial aquifer. In the northern sector, where the depth of groundwater is variable between 38,00 m from ground level (inland areas) to 1,00 m from ground level (along the coast), the practiced agricultural activities, are different from those of the southern sector of the plain (olive trees, citrus groves, arable land, etc.), but here there are too tourist facilities and private houses along the coast. These various activities contribute, even in this area to outline a potential risk of pollution to the superficial aquifer of S. Eufemia Lamezia plain which, however, is slightly less worrying than in the south sector.